Multi-foci laser separation of sapphire wafers with partial thickness scanning - Lye, Celescia Siew Mun (2022)
With multi-foci laser cutting technology for sapphire wafer separation, the entire cross-section is generally scanned with single or multiple passes. This investigation proposes a new separation technique through partial thickness scanning. The energy effectivity and efficiency of the picosecond laser were enhanced through a two-zone partial thickness scanning by exploiting the internal reflection at the rough exit surface. Each zone spanned only one-third thickness of the cross-section, and only two out of three zones were scanned consecutively. A laser beam of 0.57 W and 50 kHz pulse repetition rate was split into 9 foci, each with a 2.20 μm calculated focused spot diameter. By only scanning the top two-thirds sample thickness, first its middle section then upper section, a cleavable sample could result. This was achieved with the lowest energy deposition at the fastest scanning speed of 10 mm/s investigated. Although with partial thickness scanning only, counter intuitively, the cleaved sample had a previously unattained uniform roughened sidewall profile over the entire thickness. This is a desirable outcome in LED manufacturing. As such, this proposed scheme could attain a cleavable sample with the desired uniformly roughened sidewall profile with less energy usage and faster scanning speed.